TINJAUAN TEORITIS MANAJEMEN MUTU PENDIDIKAN - Na'im, Zaedun (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2024)
When discussing the results of educational provision, of course you will question the quality of educational provision, and to measure the quality of education you can look at the graduates or output. And this can be realized if it is done with proper management of the quality of education, and that is the domain of education quality management studies. So a comprehensive understanding of education quality management is needed so that it can be implemented in educational institutions appropriately and can run effectively and efficiently. In this study the author uses qualitative research with a library research approach and is descriptive in nature, where the author wants to reveal a deeper theoretical review of education quality management." The result of this study is that quality management, which is more popularly known as TQM, is a way of continuously improving performance (continuous performance improvement) at every level or process, in every functional area of an organization by using available human resources and capital. The main goal of TQM in education is to improve the quality of education in a sustainable, continuous and integrated manner. Meanwhile, the success of TQM is largely determined by its five supporting pillars, namely: 1). Product, 2) process, 3) organization, 4) leadership, and 5) commitment. And the implementation of quality management in schools, among other things, focuses on a). Implementation of institutional management, b). Implementation of curriculum quality management, c). Implementation of learning management and graduates